2019
DOI: 10.1017/s1049023x19000177
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of Medical and Public Health Coordination - Experience from the 2016 Kumamoto, Japan Earthquake

Abstract: Objective:The aim of this study was to identify disaster medical operation improvements from the 2016 Kumamoto Earthquake (Kumamoto Prefecture, Japan) and to extract further lessons learned to prepare for future expected major earthquakes.Methods:The records of communications logs, chronological transitions of chain of command, and team registration logs for the Disaster Medical Assistant Team (DMAT), as well as other disaster medical relief teams, were evaluated.Results:A total of 466 DMAT teams and 2,071 DMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 8 publications
(8 reference statements)
0
13
0
Order By: Relevance
“…The vast majority of articles that were excluded during screening were anecdotal personal accounts of a health care provider's response to a disaster where no evaluative component was reported. Of the 37 papers included in the analysis, 9 related to infectious disease outbreaks (H1N1 in uenza, Ebola virus, Severe Acute Respiratory Syndrome(SARS)) (Table 1) (12)(13)(14)(15)(16)(17)(18)(19)(20); 19 related to extreme weather events (hurricanes, typhoons, severe storms) (Table 2) (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), and 10 related to natural disasters (earthquakes, tsunamis) (Table 3) (40)(41)(42)(43)(44)(45)(46)(47)(48)(49). Twenty-four of the papers (65%) were observational/descriptive papers, seven (19%) were qualitative or mixed-methods case studies, two (5%) reported on survey data, two (5%) on qualitative studies, two (5%) were systematic reviews, and one (2.5%) was a quantitative study.…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of articles that were excluded during screening were anecdotal personal accounts of a health care provider's response to a disaster where no evaluative component was reported. Of the 37 papers included in the analysis, 9 related to infectious disease outbreaks (H1N1 in uenza, Ebola virus, Severe Acute Respiratory Syndrome(SARS)) (Table 1) (12)(13)(14)(15)(16)(17)(18)(19)(20); 19 related to extreme weather events (hurricanes, typhoons, severe storms) (Table 2) (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), and 10 related to natural disasters (earthquakes, tsunamis) (Table 3) (40)(41)(42)(43)(44)(45)(46)(47)(48)(49). Twenty-four of the papers (65%) were observational/descriptive papers, seven (19%) were qualitative or mixed-methods case studies, two (5%) reported on survey data, two (5%) on qualitative studies, two (5%) were systematic reviews, and one (2.5%) was a quantitative study.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, those affected by disasters are vulnerable to infectious diseases due to overcrowded shelters, environmental changes, and poor personal hygiene. 20 Furthermore, since many people have refrained from social interactions for fear of infection, various support activities that have been carried out in the past disasters, such as child care, transportation of supplies, and soup kitchens, 21 may be reduced. In order to ensure access to medical services even in such a situation, it is also important to share information on hospitals and evacuation centers where medical treatment is available, and to expand telemedicine services.…”
Section: Discussionmentioning
confidence: 99%
“…Public health studies on coordination units for managing mass casualty incidents caused by accidents or natural disasters have been performed. So-called Disaster Medical Assistant Teams are used in various countries and can also support the logistical organization, but economic analyses are lacking [ 13 - 16 ].…”
Section: Discussionmentioning
confidence: 99%